Application of Systems Thinking to Health Policy & Public Health Ethics : Public Health and Private Illness - Battle-Fisher, Michele (SpringerBriefs in Public Health,, 2015)
This book looks at health policy through the lens of public versus private: population health versus the somatic, social, or emotional experiences of a patient. Rather than presenting policy/ethics as overly technical, this book takes a novel approach of framing public and private health in terms of political philosophy, ethics, and popular examples. Each chapter ties back to the general ethics or political literature as applicable, which are not customarily parts of the current public health curriculum. The author's work on the Orgcomplexity blog has touched on this subject by systemically exploring public policy issues, and the tone of this book mimics the blog with an extension of the arguments.